Karakteristik Proximate dan Fisika Premium Fish Patties (Clarias sp.) dengan Formulasi Subtitusi Daging Ayam Potong (Gallus gallus domesticus) - Bayu Kusuma; Sri Dayuti; Eko Waluyo; Angga Wira Perdana; Ahmad Fahmi Syihab Q.R.M.; Intan Yusuf Habibie (JFMR (Journal of Fisheries and Marine Research), 2020)
The use of catfish for premium fish patties products has a weakness in the low of gel strength. The substitution of catfish with chicken is expected to solve this problem. Three substitution formulations of catfish using chicken were carried out experimentally to determine the proximate variables and physics of premium fish patties. The results showed that the substitution of catfish using chicken in premium fish patties greatly affected the physical characteristic, especially texture. This is in contrast to the results that the substitution treatment does not affect the proximate and color characteristics.